If the solution to x − y − 1 + ( x + y + 2 ) y ′ = 0 is A 1 ln ( ( x + 0 . 5 y + 1 . 5 ) B + 1 ) + tan − 1 ( x + D / 2 y + C / 2 ) = k 1 − ln ( x + 2 1 )
where k 1 is the arbitrary constant of integration , determine A + B + C + D given that each unknown is a positive integer.
(This problem is part of the set Extraordinary Differential Equations .)
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Perfect solution
Firstly Lets replace x by x'+h and y by y'+k
Now we adjust h and k such that constant terms vanishes and we get a homogeneous differential equation
doing so we obtain h = -0.5 and k = -1.5
Now substitute y' = vx' which is a standard substitution for solving homogeneous differential equations .
on solving we get the required answer
ain't i right bro ?
it can be done without pen and paper and i did so, observe carefully , you would see how ! since the given form contains y+1.5 ad x+0.5 all over , it was a hint what would be C=3 , D=1 so , you need not do what bro @Prakhar Bindal has done if you watch closely and do some calculation (again in mind:P) you would get A=B=2 so, i recommend you too to do the questions in mind without making yourself work to get paper and pen , laziness rocks !
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Variable changes in linear differential equations of first order: y'=f(t,y)
Instead of coupling the x and y terms together within the same substitution V = x + y + α into the ODE for some constant α , notice that this method does not work here because there are no viable values for α such that the ODE becomes separable or homogeneous.
Therefore, we try using two substitutions instead: X = x + α and Y = y + β and find suitable values for real-valued constants α and β such that the ODE becomes homogeneous (notice that also y ′ = Y ′ ): X − Y − α + β − 1 + ( X + Y − α − β + 2 ) y ′ = 0 → X − Y + ( X + Y ) Y ′ = 0 which means we need to solve − α + β − 1 = 0 and − α − β + 2 = 0 which gives α = 1 / 2 and β = 3 / 2 .
Using the substitution W = Y / X ⟹ Y ′ = W + X W ′ we get 1 − W + ( 1 + W ) ( W + X W ′ ) = 0 the solution to which is 2 1 ln ( W 2 + 1 ) + tan − 1 W = c 1 − ln X Back substitution of the original terms gives 2 1 ln ( ( x + 0 . 5 y + 1 . 5 ) 2 + 1 ) + tan − 1 ( x + 1 / 2 y + 3 / 2 ) = k 1 − ln ( x + 2 1 ) Therefore A + B + C + D = 2 + 2 + 3 + 1 = 8 .